Ship-driven biopollution: How aliens transform the local ecosystem diversity in Pacific islands. (May 2021) - Ardura, Alba; Fernandez, Sara; Haguenauer, Anne; Planes, Serge; Garcia-Vazquez, Eva
Abstract: Ships moving species across the oceans mix marine communities throughout latitudes. The introduction of new species may be changing the ecosystems even in remote islands. In tropical Pacific islands where maritime traffic is principally local, eDNA metabarcoding and barcoding revealed 75 introduced species, accounting in average for 28% of the community with a minimum of 13% in the very remote Rangiroa atoll. The majority of non-native species were primary producers –from diatoms to red algae, thus the ecosystem is being transformed from the bottom. Primary producers were more shared among sites than other exotics, confirming ship-mediated dispersal in Pacific marine ecosystems. Limited alien share and an apparent saturation of aliens (similar proportion in ports of very different size) suggests the occurrence of "alien drift" in port communities, or random retention of newly introduced aliens that reminds genetic drift of new mutations in a population. Highlights: French Polynesian coral reefs have high proportion of alien species. In small remote atolls >13% of exotic species were found Alien contained more primary producers than the native, showing biodiversity changes from the bottom of the trophic chain. Saturation of exotics in communities and effect of "alien drift"– retention of alien species if a niche is empty. Robust study based on a NGS metabarcoding + eDNA and individual barcoding of specimens taxonomically identified de visu. Highlight the need of participation of locals and tourists in the conservation of tropical coral reefs: citizen science.